Optimalisasi Aset Wakaf Kabupaten Pakpak Bharat: Kebijakan Peningkatan Kesadaran Masyarakat dan Pembentukan Lembaga Pengelola Profesional - Linda Fitri (JURNAL ILMIAH GEMA PERENCANA, 2025)
This Policy Paper outlines that waqf management in Pakpak Bharat Regency faces significant challenges due to the absence of a professional district-level waqf management institution, poor coordination among stakeholders, and the incomplete legalization and documentation of waqf assets. This condition results in the suboptimal utilization of waqf land, which has significant potential to support community welfare. This article uses a qualitative method with a descriptive analysis approach. Alternative policy analysis uses the William N. Dunn scoring method. The most recommended policy is the establishment of a District-Level Waqf Management Institution through the issuance of a Minister of Religious Affairs Regulation governing its formation, structure, and work procedures, as well as its integration with the Indonesian Waqf Board (BWI). This policy was chosen because it is considered the most effective in strengthening coordination, guidance, and supervision of sustainable waqf asset management, accelerating waqf land certification, and ensuring integrated waqf asset documentation. The implementation of this institution is also expected to increase the capacity of Nazhir through training and certification, so that waqf management becomes more professional and productive. This regulatory support will strengthen the legitimacy and sustainability of waqf management, reduce the potential for disputes, and expand the distribution of waqf benefits to the community. With the existence of an official institution at the district level, the Ministry of Religion can ensure more structured, transparent, and accountable waqf management, while simultaneously making waqf a strategic instrument for regional socio-economic development.